Corrective feedback in the teaching of english language among federal university lecturers in South-West, Nigeria (2020)
This study examined English grammar and phonology classes. The study made use of Descriptive survey design. The population of the study comprised undergraduate English Language lecturers and their students in South-West. Nigeria Purposive sampling technique was used to select fifteen {15) English Language University lecturers taking English Grammar and phonology and 350 undergraduate students in South-West Federal Universities. Three research questions were answered. Lecturer Classroom Interaction Sheet (LCIS) with reliability co-coefficient of 0.76 and Students’ Rating of English Language Lecturer Corrective Feedback (SRELLCF) with the reliability co-efficient of 0.78 were the instruments used for data collection. Data was analyzed using descriptive statistics and T-test. The study revealed that explicit correction is the most (44.4%) commonly use types of reformulation corrective feedback while correcting wrong sentences in absence of communication problem among the lecturers is the least (3.7%) form of reformulation corrective feedback. In term of prompt corrective feedback, offering some comments without directly correcting the error is the most (4 1.6%) commonly use while providing brief explanation to allow student to self-correct and asking questions to get the Correct form from student (s) are the least (8.3%) patterns of prompt corrective feedback. The study further revealed that there was a significant difference in score between the two groups of lecturers, t (13.83) = -00, p < .05, two-tailed where the experienced (M = 67.38, SD = 7.03) scoring higher than inexperienced lecturers (M - 58.43, SD = 4.75). The magnitude of mean difference is 4.95 There was a significant difference in score between the two groups of lecturers, t (13,83) = .00. p < .05, two-tailed where Ph.D. holders (M = Io < 8VuD =8 03) Scoring higher than MA’ holders <M =<5843. SD - 5.75). The magnitude of mean difference is - The study then recommends that Lecturers should be able to implement a variety of corrective feedback patterns and adapt the specific patterns they use to the particular learners they are teaching.